2016
DOI: 10.1186/s12906-016-1235-5
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro inhibition of rat liver glutathione transferases activity by extracts from Combretum zeyheri (Combretaceae) and Parinari curatellifolia (Chrysobalanaceae)

Abstract: BackgroundParinari curatellifolia and Combretum zeyheri are medicinal plants used in Zimbabwe and other Southern African countries for stomach ailments, fever, body aches, wound healing, cancer and tuberculosis. Glutathione transferases (GSTs) are mammalian enzymes that play a significant role in the detoxification and metabolism of many xenobiotic and endogenous compounds and as such can interact with many exogenous compounds including herbal medicines.The effects of Parinari curatellifolia and Combretum zeyh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…In our case, free radical damage of the active sites of antioxidant enzymes might be a possible cause for the decline in enzymes' activity of spinosad-treated Sf9 cells. GST is a key enzyme of cellular detoxification systems, which is important for antioxidant protection and xenobiotic metabolism (Gweshelo, Muswe, & Mukanganyama, 2016). In the present study, the GST activity was increased in Sf9 cells that were exposed to both spinosad concentrations (Figure 1(D)).…”
Section: Discussionsupporting
confidence: 57%
“…In our case, free radical damage of the active sites of antioxidant enzymes might be a possible cause for the decline in enzymes' activity of spinosad-treated Sf9 cells. GST is a key enzyme of cellular detoxification systems, which is important for antioxidant protection and xenobiotic metabolism (Gweshelo, Muswe, & Mukanganyama, 2016). In the present study, the GST activity was increased in Sf9 cells that were exposed to both spinosad concentrations (Figure 1(D)).…”
Section: Discussionsupporting
confidence: 57%
“…Anemia (Peter et al, 2014), Angola: cough, black magic, provokes abortion (Bossard, 1996); Burundi: laxative, vomiting, against black magic, chest pain, colic, psychose (Baerts and Lehmann, 1989); Central African Republic: tuberculosis (Boulesteix and Guinko, 1979); Ivory Coast: cough (Ambe and Malaisse, 2000); Mali: trypanosomiasis (Bizimana et al, 2006); Namibia: HIV/AIDS, herpes simplex, tuberculosis, diarrhea (Chinsembu and Hedimbi, 2010); Tanzania: tachycardy (Chabra and Mahunnah, 1994); Togo: pinworms, epilepsy, psychose (Adjanohoun, 1986); Uganda: stomachache, jaundice (Segawa and Kasenene, 2007); Zimbabwe: diarrhea (Chinemana and Drummond, 1985), sedative, uterine disorders (Gelfand et al, 1985), constipation, toothache (Maroyi, 2013) Antioxidant (Karou et al, 2011), antioxidant and hepatoprotective (Atawodi et al, 2013), antimicrobial (More et al, 2008), antimycobacterial (Chimponda and Mukanganyama, 2010), antibacterial (Peni et al, 2010), cytotoxicity (Gororo et al, 2016), cytoprotective (Gweshelo et al, 2016), hepatoprotective (Olaleye et al, 2014) Paropsia brazzaeana Congo: rheumatism, pain, amoebic dysentery; Zimbabwe: gonorrhea, toothache (Neuwinger, 2000) Antidiarrhoeic, antibacterial, antiamoebic and antispasmodic (Tona et al, 1999), antiamoebic (Tona et al, 1998)…”
Section: Parinari Curatellifoliamentioning
confidence: 99%
“…Glutathione-S-Transferase performs a crucial function in the detoxi cation of many endogenous and xenobiotic compounds (51). In a report, it was revealed that 6-gingerol recovered the activities of GST, SOD, and GSH in diethylnitrosamine (DEN) intoxicated in adult male albino rats (52).…”
Section: Discussionmentioning
confidence: 99%